Investigating the Variances of Maghrib Prayer Time in Indonesia and Malaysia - Afifi, Filza Noor Rikzal; Umar, Roslan; Hidayah, Vika Rachmania (Al-Hilal: Journal of Islamic Astronomy, 2025)
The determination of the beginning of Maghrib prayer time is crucial, as it is directly related to the position of the Sun on the western horizon. Indonesia sets the Maghrib time when the Sun is at the proper position of -1 degree or -0° 50', along with elevation and atmospheric refraction corrections. In contrast, Malaysia adds approximately two minutes after sunset without defining a specific angular position, considering local elevation and atmospheric factors. This study aims to comparatively analyze the methodologies used by Indonesia's Ministry of Religious Affairs and Malaysia's JAKIM through a library research approach, employing both philosophical-normative and astronomical perspectives. Data were collected from interviews and Islamic astronomy documents. The findings show that while both countries agree on the Islamic legal principle that Maghrib begins when the Sun has fully set, technical differences in calculation methods reflect their respective approaches to integrating religious texts with astronomical precision.